Recarving of Roman portraits in Late Antiquity : from face to face - Prusac, Marina. (Monumenta Graeca et Romana, 2010)
This book is based on an investigation of more than 2000 portraits of which around 500 have proven to be recarved. It provides thorough analyses of the different recarving methods, some of which can be attributed to geographically localized workshops, establishing classifiable categories, and an analytical text with special regard to the cultural historical changes in Late Antiquity. The investigation underpins a hypothesis on the late antique portraits style as a consequence of the many recarved portraits at the time, which relied on a syncretism of politics, religion and ideology. The conclusion gives a new understanding of how broad-scoped, culturally and politically encoded and comprehensive the practice of recarving was.